2024
DOI: 10.1037/tra0001371
|View full text |Cite
|
Sign up to set email alerts
|

After Hurricane Maria: Effects of disaster trauma on Puerto Rican survivors on the U.S. mainland.

Abstract: Purpose: In September 2017, Hurricane Maria devastated Puerto Rico. Houses were destroyed, millions of people lost power and access to clean water, and many roads were flooded and blocked. In the years following the storm, hundreds of thousands of people have left Puerto Rico and settled on the U.S. mainland. The purpose of this study is to examine the impact of disaster trauma among Puerto Rican adults who moved to the U.S. mainland after Hurricane Maria. Method: Participants were 319 adult Puerto Rican Hurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…This seems to suggest that, when considering online xenophobia and offline experiences of discrimination, both are important risk factors of comparable magnitude. This is a critical finding for migration-related cultural stress and crisis migration researchers, as work within these paradigms has tended to focus on in-person experiences while overlooking experiences occurring in the online realm (e.g., Montero-Zamora et al, 2023; Salas-Wright & Schwartz, 2019; Salas-Wright et al, 2021; Schwartz et al, 2022; Zeledon et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest that, when considering online xenophobia and offline experiences of discrimination, both are important risk factors of comparable magnitude. This is a critical finding for migration-related cultural stress and crisis migration researchers, as work within these paradigms has tended to focus on in-person experiences while overlooking experiences occurring in the online realm (e.g., Montero-Zamora et al, 2023; Salas-Wright & Schwartz, 2019; Salas-Wright et al, 2021; Schwartz et al, 2022; Zeledon et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are likely multiple reasons for this, one potential explanation involves the potential predictive link between hurricane stress and cultural stress. Two cross-sectional studies conducted by our research group, one with Hurricane Maria survivors on the U.S. mainland (Schwartz et al, 2022) and another with Venezuelan immigrants in Colombia and the United States (Vos et al, 2022), have found that premigration crisis-related stressors may predict postmigration cultural stress. Although the research designs used in these studies do not permit us to draw directional conclusions, the hypothesis suggested by these two sets of findings—in two different populations—is that stressors occurring prior to migration, and that may have helped to prompt the migration, may predispose individuals toward experiencing or perceiving cultural stress in the destination country or region.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step, our community partner organization (i.e., the Episcopal Church of Jesus of Nazareth in Orlando) referred initial seed participants to the study in Orlando, Florida. As described by Schwartz et al (2022), approximately half of all parishioners in the church are Hurricane Maria survivors and have identified the church as a key cultural pillar to start their new lives in Central Florida. Therefore, after identifying initial seed participants, two church staff members and two recruiters on the research team collaborated to invite eligible individuals (i.e., recently arrived Hurricane Maria survivors who were 18 years or older) who provided informed consent to access the study website and to complete the study measures online.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from other Hispanic groups, including Venezuelans (Salas-Wright, Oh et al, 2021), as well as Mexicans and Cubans (Schwartz et al, 2015), suggest that migrants who perceive their receiving context as negative are also likely to report elevated symptoms of depression and anxiety. Among Hurricane Maria survivors specifically, such perceptions also may be likely to exacerbate the association between hurricane trauma and internalizing symptoms (Schwartz, Montero-Zamora, et al, 2022). Identifying perceptions of a negative context of reception, then, may be helpful in guiding counselors toward a potential trigger for depression and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For research, the Negative Context of Reception Scale represents a tool for assessing a key cultural stressor that, along with experiences of discrimination, can marginalize and emotionally harm individuals who have already been traumatized by a natural disaster and subsequent relocation. Indeed, a growing body of work has begun examining discrimination and negative context of reception together (e.g., Salas-Wright, Goings et al, 2021; Schwartz, Montero-Zamora, et al, 2022)—and these variables often both account for significant variability in symptoms of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%